PENERAPAN STRATEGI PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN PRESTASI BELAJAR IPA - Masra, Masra (Jurnal Pendidikan Guru, 2018)
This study aims to improve the learning achievement of science of human senses equipment materials by applying STAD type cooperative learning strategy in fourth grade students of SDN 123 Pekanbaru. This research was conducted at SD Negeri 123 Pekanbaru. The subject of this research is the fourth grade students of SDN 123 Pekanbaru T.A 2016/2017. The fourth grade students of SDN 123 Pekanbaru require 29 students. Techniques used to collect data in this study are test, Non-test (Observation / observation, interview, and documentation). This study was conducted by applying STAD type cooperative learning that has been done for three cycles, it can be concluded with STAD type cooperative learning has a positive impact in improving learning achievement of human senses material in fourth grade students of SDN 123 Pekanbaru. This is evident from the average number of classes only for 68.96, with the number of students who "complete" only as many as 12 students (41.38%), while the students are "not complete" as many as 17 students (58.62%), The average value in grade II is 75.17, with the total number of students who are "complete" only 17 students (58.62%), the students are "unfinished" as many as 12 students (41.38%) the average grade in cycle III was 88.97, with the total number of students "complete" only as many as 27 students (93.10%), while the students are "unfinished" as many as 2 students (6.90%). STAD can improve learning achievement ipa material of the human senses in fourth grade students of SDN 123 Pekanbaru.